2021
DOI: 10.3390/healthcare9010037
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Method for RT-PCR Detection of SARS-CoV-2 in Clinical Samples

Abstract: Introduction: the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic of acute respiratory disease (COVID-19). SARS-CoV-2 is a positive-strand RNA virus and its genomic characterization has played a vital role in the design of appropriate diagnostics tests. The current RT-PCR protocol for SARS-CoV-2 detects two regions of the viral genome, requiring RNA extraction and several hours. There is a need for fast, simple, and cost-effective detection strategies. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Fever was the most observed symptom (69%), followed by cough (34.3%) and rhinorrhoea (29.2%). In comparison, previous reports noted fever as the most observed symptom, ranging between 41% and 59% cases, while cough was the second most prominent symptom (37%–46%) 26–34…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Fever was the most observed symptom (69%), followed by cough (34.3%) and rhinorrhoea (29.2%). In comparison, previous reports noted fever as the most observed symptom, ranging between 41% and 59% cases, while cough was the second most prominent symptom (37%–46%) 26–34…”
Section: Discussionmentioning
confidence: 60%
“…In comparison, previous reports noted fever as the most observed symptom, ranging between 41% and 59% cases, while cough was the second most prominent symptom (37%-46%). [26][27][28][29][30][31][32][33][34] Only 3.85% patients in our cohort developed complications, with the most common being bacterial infection (40.0%), ARDS (13.3%) and shock (13.3%). Furthermore, Open access we found that dyspnoea, abnormal chest radiographic findings, lethargy, elevated initial ferritin and elevated D-dimer were significantly associated with the development of complications in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our protocol increases the testing capacity during the period limited supplies. In another recent study to assess lab-developed direct RT-qPCR, only specific types of virus containers or other pretreatments were used [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have tried different thermal shock protocols as an extraction-free technique to detect SARS-CoV-2 ( Beltrán-Pavez et al, 2021 ; El-Kafrawy et al, 2021 ; Fomsgaard and Rosenstierne, 2020 ; Pearson et al, 2020 ; Smyrlaki et al, 2020 ). Based on these data, we tested two different thermal shock techniques.…”
Section: Discussionmentioning
confidence: 99%